Application of ISO 27001 and its influence on the information security of a Peruvian private company - Rodriguez Baca, Liset Sulay (2020)
The advancement of technology in the worldcauses, among other aspects, the handling of important information, which can be considered as fundamental for the strategic interests of companies. The objective of the research was to analyze the influence of the application of ISO 27001 on the information security of a private company in Lima (Peru). Based on the application of a quantitative methodology, a pre-experimental study was used in which the influence of the application of ISO 27001 was determined. To this end, a sample of 30 employees of the company was considered. The quantitative conclusion shows that there is an influence of the application of ISO on information security and the dimensions of confidentiality, integrity and availability.